Comparison between Kriging and Lognormal Kriging for Sulfur Data (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper deals with the spatial estimation to be optimal estimate when the data have anormal distribution. Ordinary kriging technique used in this research and lognormalkriging after take logarithm of original data. Variogram function uses in this research toobtain the best model of covariance function. The objective of this research is to assess theresistance of ordinary kriging and lognormal kriging to outliers. The data adopted of thispaper from hydrogeological hydro chemical study of Mosul Governorate /Iraq. From theresults, the errors in the estimated value are critical for the log variance. These resultsshow that ordinary lognormal kriging is more effect than ordinary kriging technique underoutlier.